Effect of CaO on the Autogenous Shrinkage of Alkali-Activated Slag Mortar - Dengdeng Zheng; Tao Ji; Guojie Wang (Advances in Materials Science and Engineering)
The autogenous shrinkage of alkali-activated slag (AAS) is significantly higher than that of ordinary Portland cement (OPC). The higher risk of concrete cracking due to autogenous shrinkage is a critical drawback to wider use of this promising alternative binder. The effect of CaO content on the autogenous shrinkage of AAS mortar was investigated. The autogenous shrinkage of AAS mortars was determined by comparator. The pore structure of the pastes was determined by mercury intrusion porosimetry. The hydration products of the pastes were determined by Fourier transform-infrared, thermogravimetric analysis, X-ray diffraction, and 29Si solid-state magic-angle spinning nuclear magnetic resonance. The results show that the amount of portlandite increases as CaO content increases. CaO in the paste causes the partial replacement of C-S-H(I) (low stiffness) by C-S-H(II) (high stiffness). The hydration reaction of AAS is inhibited by the addition of CaO. The increase of polymerization degree of C-(A-)S-H and rearrangement of C-S-H(I) during hydration are inhibited by the addition of CaO, and micropores closure is also inhibited. Therefore, the autogenous shrinkage of AAS mortar decreases with the increase of CaO content.